Sociodemographic correlates of prospective dog owners’ intentions to participate in controlled trials of dog ownership and human health - Debbie Chia (BMC Research Notes, 2018)
Abstract Objective Dog ownership is popular, with research suggesting improvements in physical and psychological health of dog owners. However, majority of these studies were not investigator-controlled. Ethical and practical implications arising from the intervention exposure (dog ownership) result in recruitment difficulties. A fit-for-purpose design, such as delaying dog adoption until after data collection, could alleviate such issues. The purpose of this study was to explore intentions and possible incentives for participation in investigator-controlled trials examining the effects of dog ownership on human physical and psychological health. Results Female (OR 1.64, 95% CI 1.31–2.04) and older (OR 65+ years 1.49, 95% CI 1.06–2.10) participants were more likely to be interested in taking part in a study investigating the health benefits of dog ownership. Majority reported no incentive was necessary for participation (57%), while others preferred pet food supplies (37%), or vouchers for veterinary care (32%). Over half of participants (53%) were willing postpone adoption for up to 3 months to participate in an investigator-controlled trial. The results of the study, showing majority of participants interested in participating in future studies examining the health benefits of dog ownership and without incentives, provides insight to methodical directions for future studies.